The French Annales School and its impact on history - Dr.Hussein Saad Hanouf AL-Suirawi (Journal of College of Education, 2025)
The French Annales School introduced new and innovative ideas, concepts and mechanisms in historical writing by avoiding narrative history and moving towards studying economic, social and cultural structures, and expanding its concept of the document to include all types of documents. We find a shift in the interest of Annales historians from studying the particular to studying the general, from studying the part to studying the whole, and from interest in the individual to studying society.